Evaluación de riesgos físicos-mecánicos y su incidencia en la salud y seguridad ocupacional de los trabajadores en la empresa Producom - Bailón Salvatierra, Pedro Andrés (2017)
This research aimed to evaluate the physical and mechanical risks and their impact on the health and occupational safety of the company's workers Production, through: the determination of physical and mechanical risks through the matrix of the Ministry of Labor Relations, weighting of occupational health and safety and the preparation of corrective measures on risks in the company. For the risk weighting, a description of the work areas, the activities carried out, the identification of the hazards and the assessment of the existing risks were carried out. The company has 9 work zones: 1: Heavy, 2: Product review, 3 and 4: Warehouse, 5: Dryer, 6: Peeler / Cleaner, 7: Silo warehouse, 8: (19 risks) Frequent is the one of attack or the hit with vehicles by the amount of automotive that mobilize daily. Weighted physical risks were 5, three of them high risk, and of the 18 hazards identified mechanically, and 10 were rated as high hazard. For weighted risks, a series of measures are presented, presented and approved by the company representative. Safety and occupational health is affected by the risks found in the company, becoming visible in diseases such as headaches, irritability in the senses of sight or hearing, minor injuries in extremities and muscular fatigue.